2020
DOI: 10.1161/circulationaha.119.041297
|View full text |Cite
|
Sign up to set email alerts
|

Resource and Infrastructure-Appropriate Management of ST-Segment Elevation Myocardial Infarction in Low- and Middle-Income Countries

Abstract: The 143 low- and middle-income countries (LMICs) of the world constitute 80% of the world’s population or roughly 5.86 billion people with much variation in geography, culture, literacy, financial resources, access to health care, insurance penetration, and healthcare regulation. Unfortunately, their burden of cardiovascular disease in general and acute ST-segment–elevation myocardial infarction (STEMI) in particular is increasing at an unprecedented rate. Compounding the problem, outcomes remain suboptimal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 64 publications
3
49
0
7
Order By: Relevance
“…Our results are relevant for national practice, as STEMI 30-day mortality in Mexican patients has been reported as high as 27% (23), the highest among OECD countries, and reperfusion rates have been reported as low as 52.6% (24). A recent whitepaper positions PIs as a uniquely attractive option for patients in LMICs, since access to pPCI is limited and unfrequently achieved within the guideline-mandated times (11). In the present study, only 11.0% of the patients from the pPCI group were treated within the guideline mandated timelines (<120 min) (3), which suggests that PIs may be a solid option to improve outcomes in the remaining 89% of patients who cannot access timely pPCI.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
See 2 more Smart Citations
“…Our results are relevant for national practice, as STEMI 30-day mortality in Mexican patients has been reported as high as 27% (23), the highest among OECD countries, and reperfusion rates have been reported as low as 52.6% (24). A recent whitepaper positions PIs as a uniquely attractive option for patients in LMICs, since access to pPCI is limited and unfrequently achieved within the guideline-mandated times (11). In the present study, only 11.0% of the patients from the pPCI group were treated within the guideline mandated timelines (<120 min) (3), which suggests that PIs may be a solid option to improve outcomes in the remaining 89% of patients who cannot access timely pPCI.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
“…However, it is noteworthy that access to reperfusion therapy is still limited in several countries, and great heterogeneity in treatment and mortality rates exists (4). For example, previous studies have reported lower rates of reperfusion therapy in LMICs 3, where access to either fibrinolytics or pPCI might be challenging due to the lack of awareness, severe paucity of resources, and lack of STEMI systems of care (11). The difficulties for the delivery of timely reperfusion therapy in large metropolitan areas have also been identified (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, to our knowledge, is the first retrospective study to examine the impacts of the regionalization of STEMI care, including the combined QI initiatives and the establishment of the information sharing system between the MPDS and the hospital-based CPC registry. The findings have implications for further promoting the measures, with the ongoing engagement of QI efforts and for their potential implementation in low- and middle-income settings where the burden of STEMI is increasing at an unprecedented rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…thrombolysis followed by angiography and, if indicated, percutaneous coronary intervention [PCI]), has resulted in a fall in STEMI mortality, particularly in developed countries 5 ; however, in low-and middle-income countries (LMICs), where 80% of all cardiovascular deaths occur, lack of an appropriate care system is the most important barrier to implementing guidelinebased STEMI treatment. 6 A considerable number of STEMI patients, especially in LMICs, are not offered any reperfusion therapy, particularly PPCI which is the preferred reperfusion strategy in STEMI patients. 5 A study in China showed that the in-hospital mortality rate of STEMI in county-level hospitals was 3-times higher than province-level hospitals (10.2% vs. 3.1%, respectively), partly due to hospital facilities and reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%